Bi-decadal changes in nutrient concentrations and ratios in marine coastal ecosystems: The case of the Arcachon bay, France. (February 2022) - Lheureux, A.; David, V.; Del Amo, Y.; Soudant, D.; Auby, I.; Ganthy, F.; Blanchet, H.; Cordier, M-A.; Costes, L.; Ferreira, S.; Mornet, L.; Nowaczyk, A.; et al.
Graphical abstract: Highlights: [NOx ], [NH4 + ] and [Si(OH)4 ] increased but [PO4 3− ] decreased between 2000 and 2019. Seagrass meadow decline directly and indirectly explained through: Reduced nutrient consumption and sediment stabilization. Increased phytoplankton biomass with high P-need. Increase in temperature and changes in wind conditions also mattered. Abstract: Large amounts of nutrients have been released to the coastal ecosystems during the 20th century. Since then, management policies have been implemented and these amounts decreased in the economically developed countries. We examined the bi-decadal changes in nutrients (nitrate + nitrite, ammonium, orthophosphate and silicic acid) in the Arcachon bay, a semi-enclosed lagoon that hosts one of the largest but declining seagrass meadow in Europe. Seven sites have been sampled for nutrients and biogeochemical parameters during twenty years at low and/or high tide. In addition, continental and climatic data as well as hydro-climatic indices were used. Dynamic linear models were used to assess the bi-decadal changes in nutrient concentrations and ratios, their seasonality, and the bi-decadal changes of their potential drivers. Partial least square path modeling were used to investigate the relationships between potential abiotic drivers and nutrients. During the study period, the concentration of N and Si nutrients increased whereas the concentration of orthophosphate decreased, leading to deep changes in nutrient ratios. Clear relationships between abiotic drivers (local climate, continental inputs and the bay hydrodynamism) and N, P and Si nutrients were highlighted. However, the bi-decadal change in nutrient concentrations and ratios was mainly ascribed to the seagrass meadow decline through direct (less nutrient consumption) and indirect (increase in phytoplankton biomass) processes. Changes in temperature and wind direction may also influenced the nutrients concentrations through processes of remineralisation and flushing time, respectively. This study illustrates (1) the top-down control of seagrass on the nutrients concentrations and stoichiometry, and (2) the competition between primary producers (seagrass vs phytoplankton) for their nutrients resource.